BANZARE holothuroids (Echinodermata: Holothuroidea) - O’loughlin, P. Mark (Zootaxa, 2009)
The holothuroid species collected by The British, Australian and New Zealand Antarctic Research Expedition (BANZARE) are listed, with some systematic annotations. A previous report by O’Loughlin on some BANZARE holothuroids is revised and incorporated. Four new species are described: the Antarctic dactylochirotid Echinocucumis kirrilyae sp. nov.; the Kerguelen dendrochirotid Clarkiella deichmannae sp. nov.; the Antarctic dendrochirotids Trachythyone cynthiae sp. nov. and Trachythyone mackenzieae sp. nov. Cucumaria serrata var. intermedia Théel from Heard and Kerguelen, and Cucumaria serrata var. marionensis Théel from Marion, are raised to species status, and assigned to Pseudocnus Panning. Cucumaria (Semperia) ekmani Ludwig & Heding is a junior synonym of Cucumaria kerguelensis Théel. Cucumaria kerguelensis is re-assigned to Neopsolidium Pawson. Thyone recurvata Théel and Cucumaria squamata Ludwig are junior synonyms of Trachythyone muricata Studer. Cucumaria (Semperia) bouvetensis Ludwig & Heding is formally re-assigned to Trachythyone. Trachythyone baja Hernández is a junior synonym of Trachythyone bouvetensis (Ludwig & Heding). Molecular genetic data indicate possible allopatric cryptic Antarctic forms for the morpho-species Laetmogone wyvillethomsoni Théel. A table with all species and station data is provided.